Moringa oleifera: A Review of Pharmacological Benefits - Al-Shahat, Dina S.; Abo-Elmaaty, Azza M.A.; Kamel, Mohamed A. (Journal of Advanced Veterinary Research, 2022)
The chemical composition of a specific material, the structure that gives it its unique qualities, and indirectly the method of production all has an impact on the selection of an effective bioactive material for medical applications. Moringa is a type of medicinal plant with unique active ingredients that have been traditionally used to treat a variety of conditions. The species is also used to purify water and is recognized as a source of nutrients. The type consists of 13 species that have been extensively domesticated in Asia and Africa, M.O. one of them whose pharmacological values worried scientists to manage. The objective of this study is to provide updated and well-defined information on the traditional uses, biological characteristics, and therapeutic potential of Moringa oleifera. It will also evaluate upcoming research opportunities. PubMed, ScienceDirect, Google Scholar, and other journal articles published between 1994 and 2021 were used to gather the literature for this paper's review. The antioxidant, anti-inflammatory, anticancer, and other properties of Moringa oleifera are well known. Flavonoids, glucosides, and glucosinolates are present in significant concentrations, which activate the majority of its natural activity. We intend to shed light on this plant by outlining the traditional use and pharmacological properties of Moringa.